El teatro indigenista mexicano de los años veinte: ¿Orígenes del teatro popular mexicano actual? - Ortiz Bullé Goyri, Alejandro (Latin American Theatre Review, 2003)
This text provides a reconsideration of the theatre practices of the Teatro Sintético Mexicano or the Teatro Folklórico Mexicano and their different variations during the 20s. The objective is to corroborate the point that many of the experiences of present-day popular, indigenous or community theatre in Mexico have roots in those theatrical performances. (AOBG, in Spanish)